Regulation of alternative splicing of tumor-related RAC1b by signal transduction pathways - Jordan, Peter (2019)
In colon cancer, distinct genetic subtypes have been described and about 10% of cases carry an oncogenic mutation in the BRAF gene. These cases also show overexpression of alternative splicing variant RAC1b that encodes a protein with additional 19 amino acids resulting from in-frame inclusion of alternative exon 3b. RAC1b is a hyperactive variant that exists predominantly in the GTP-bound active conformation in vivo and promotes cell cycle progression and cell survival through activation of the transcription factor NF-κB. RAC1b overexpression functionally cooperates with the oncogenic mutation in BRAF-V600E to sustain colorectal tumor cell survival. The splicing factor SRSF1 was identified as an important key regulator of RAC1b alternative splicing in colorectal cells. It binds an exonic splice enhancer element in the alternative exon. We found that pro-inflammatory signals increase RAC1b expression in colorectal cell lines and studied how signaling pathways are involved in the deregulation of alternative splicing. The depletion of two protein kinases, SRPK1 and GSK3β, affected RAC1b levels and both do so via the phosphorylation status of splicing factor SRSF1. Reduced SRSF1 phosphorylation decreased its nuclear translocation and concomitantly the generation of RAC1b. Interestingly, GSK3β phosphorylation was identified to serve as target for the anti-inflammatory drug ibuprofen, which we previously found to inhibit RAC1b overexpression in a cyclooxygenase-independent manner. Together, our results demonstrate that oncogenic signal transduction pathways can deregulate alternative splicing in tumor cells and that pharmacological intervention with the protein kinases involved may be of therapeutic value.